Investigation of Heavy Metal Level and Mineral Nutrient Status in Widely Used Medicinal Plants' Leaves in Turkey: Insights into Health Implications - YALÇIN, BAHATTİN; ÖZYİĞİT, İBRAHİM İLKER (HUMANA PRESS INC, 2018)
The use of plants in treatments has been as old as humanity and it has preserved its popularity for centuries til now because of their availability, affordability and safeness. However, despite their widespread use, safety and quality issues have been major concerns in the world due to industrial- and anthropogenic-based heavy metal contamination risks. Thus, this study was attempted to analyze the heavy metal levels and mineral nutrient status of widely used medicinal plants in Turkey to have insights about their health implications on humans. The plant concentrations of B, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn were analyzed by ICP-OES in the leaves of 44 medical plants purchased from herbal markets of three different districts of Istanbul/Turkey. The measured lowest to highest concentrations were 0.065-79.749 mg kg(-1) B, 921.802-12,854.410 mg kg(-1) Ca, 0.020-0.558 mg kg(-1) Cd, 0.015-4.978 mg kg(-1) Cr, 0.042-8.489 mg kg(-1) Cu, 34.356-858.446 mg kg(-1) Fe, 791.323-15,569.349 mg kg(-1) K, 102.236-2837.836 mg kg(-1) Mg, 4.915-91.519 mg kg(-1) Mn, 10.224-3213.703 mg kg(-1) Na, 0.001-5.589 mg kg(-1) Ni, 0.003-3.636 mg kg(-1) Pb and 2.601-36.102 mg kg(-1) Zn. Those levels in plants were in acceptable limits though some elements in some plants have high limits which were not harmful. Variations (above acceptable limits) in element concentrations also indicated that these plants could be contaminated with other metals and that genetic variations may influence accumulation of these elements at different contents. Overall, analyzed medicinal plants are expected not to pose any serious threat to human health.
Keywords: Domestic market; Export; WHO; Phytotherapy; Alternative medicine; Macro- and microelements; Beneficial element; POSSIBLE BIOMONITOR; IRON; ISTANBUL; CHROMIUM; DISTRICT; CADMIUM; QUALITY; ELEMENT; LEAD; CR